Snow vole (Chionomys nivalis Martins) affects the redistribution of soil organic matter and hormone‐like activity in the alpine ecosystem: ecological implications. Issue 20 (29th September 2015) - Pizzeghello, Diego; Cocco, Stefania; Francioso, Ornella; Ferrari, Erika; Cardinali, Alessandra; Nardi, Serenella; Agnelli, Alberto; Corti, Giuseppe
Abstract In alpine environments, colonies of snow vole (Chionomys nivalis Martins) cause strong pedoturbation, which may affect humification process and soil organic matter (SOM) cycling, with repercussions on the hormone‐like activity of organics. We investigated the effect of snow vole pedoturbation on the chemical and spectroscopic features of soil organic fractions, and the potential hormone‐like activity of humic and fulvic acids (HA, FA). The study site was located on the high‐mountain environment of the Majella massif (central Italy). Pedoturbated and regular soils were morphologically described and characterized for pH and content of total organic carbon, total extractable carbon, HA, and FA. Both HA and FA were extracted and investigated using attenuated total reflectance/Fourier transform infrared (ATR/FTIR), nuclear magnetic resonance with high‐resolution magic angle spinning (HRMAS‐NMR), and 1H‐13C heteronuclear single quantum coherence (HSQC). HA and FA were also tested for their auxin‐like and gibberellin‐like activities. Results provide evidences that bioturbated and regular soils contain a poorly decomposed SOM, but HA and FA with a well‐defined molecular structure. The HA and FA from both bioturbated and regular soils show a hormone‐like activity with a different allocation along the soil profile. In the regular soil, the highest auxin‐like activity was shown by HA and FA from Oe1 horizon, while gibberellin‐like activity was expressed by FA from Oe2 horizon. Burrowing activity determines a redistribution of organics throughout the profile with a relatively high auxin‐like activity in the FA from straw tunnel wall (STW) and gibberellin‐like activity in the HA from vole feces (VF). The relative high presence of carboxylic acids, amides, proteins, and amino acids in the FA from STW and the aromatic moieties in the HA from VF put evidences for their different behavior. The fact that snow vole activity has modified the chemical and biological properties of SOM in these soils otherwise considered governed only by low temperature has important ecological implications such as the preservation of soil fertility and vegetal biodiversity.